SEASONAL INFLUENCE OF SOIL PROPERTIES ON POPULATION DENSITY OF Bilobella braunerae (DHERVANG 1981)- (COLLEMBOLA: NEANURIDAE) IN GRASSLAND OF SOUTHERN WESTERN GHATS - THOMAS, NISHA; KUMAR, M. G. SANAL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present study was conducted to understand the impact of soil physicochemical parameters on population density and vertical distribution pattern of a soil collembolan Bilobella braunerae in grasslands of Southern Western Ghats. The results revealed that maximum mean abundance of collembola was found during postmonsoon season (26.9) followed by monsoon (20.05) and premonsoon (7.1). Population density of organisms was high in 0-10 cm layer of soil during postmonsoon season. A vertical migration pattern was observed with increase in soil temperature and decreasing moisture content during premonsoon season. During monsoon season owing to heavy rainfall organism shows a vertical migration to 10-20 cm depth and thus lesser number of organisms were seen in 0-10 cm layer of soil .Seasons exerted a strong effect on the abundance of B. braunerae in grassland .Principal Component Analysis (PCA), was used to make the selection about soil components which directly influence the population. The first five principal components (PCs) explained more than 80% of the total variance in all seasons .The PCA showed significant effect of soil pH, organic carbon, soil moisture, temperature, phosphorous and potassium on the population density of B. braunerae.